Assessment of psychosocial parameters in adolescents seeking orthodontic treatment - Maria B. Doughan; Mohannad Khandakji; Brigitte Khoury; Joseph G. Ghafari (BMC, 2024)
Abstract Aim The aim of this study was to investigate the psychosocial impact of malocclusion and the motivation for seeking orthodontic treatment among adolescents. Methods A cross-sectional study included 102 adolescents (ages 11-18) whose malocclusion was rated using 3 occlusal indices: IOTN, DAI, and PAR. The participants answered three structured questionnaires selected to measure Oral Health Related Quality of Life (OHRQoL) through the short form of the Child Oral Health Impact Profile (COHIP), the patient's perceived impact related to orthodontics through the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ), and self-esteem through the Rosenberg Self-Esteem Scale (RSES). Independent two-tailed t-tests, one-way mixed analysis of variance (ANOVA), and Spearman's correlations were used to test various associations. Results Patients with higher malocclusion scores displayed increased psychosocial impact with weak to moderate correlations (0.2 < r < 0.3; p < 0.05), but 98% wished their teeth looked better, and 70% were unhappy about their smile esthetics. The IOTN esthetic component AC was better associated with psychosocial implications of malocclusion (p < 0.01). Self-motivated patients (over 80%) had higher impactful psychosocial scores than patients whose parents were motivated for treatment. Sex did not influence the findings. Older adolescents and bullied individuals were more affected by the psychological burden of malocclusion. Conclusion The results indicate the prevalence of psychosocial and esthetic impacts of malocclusion over oral and functional problems. PIDAQ discriminated better than COHIP between varying degrees of dental aesthetics. The results suggest that the orthodontist should explore patients' expectations of treatment outcomes, not only the chief complaint.